Adoption Behaviour of Sericulture Farmers Regarding Improved Technologies of Jorhat District of Assam - Hatibaruah, Dipankar; Dutta, Lohit Chandra; Borua, Sajib; Saikia, Hemanta (Indian Journal of Extension Education, 2021)
The research study was undertaken in the purposively selected Jorhat and Majuli (undivided) districts of Assam during the year 2018-19 with an objective to analyze the adoption behaviour of sericulture farmers regarding improved technologies and their socio- economic relationship with the adoption behaviour for enhancement of production and productivity at farmers level. Sericulture has been practiced traditionally and a large portion of rural people earn their livelihood from sericulture sector in this region. The present findings revealed that adoption of improved sericulture technologies was in medium category for majority of the respondents 76.67 per cent in eri culture, 66.67 per cent in muga culture and 76.67 per cent in mulberry culture. Due to lack of awareness of improved sericulture technologies as well as poor living conditions the adoption level of sericulture technologies among the seri farmers of Jorhat district was very low. There was gap in dissemination and adoption of improved sericulture technologies in pre and post cocoon sector for growth and development of sericulture in acreage of food plants, rearing of silkworm and production and productivity of cocoon and silk. Hence, the study recommends that adoption of scientific technologies among the seri farmers has significant impact on growth and development of sericulture as well as economic benefit of the farmer.